IFRS vs Bacen Gaap: Accounting Information’s Value Relevance of the Brazilian Financial Institutions - Mariana Titoto Marques (BBR: Brazilian Business Review, 2022)
Brazilian financial institutions that have an Audit Committee and/or are listed on the Stock Exchange are obliged to disclose their financial statements in Bacen GAAP and IFRS. This study compares their relevanceusing the Ohlson Model (1995) adding control variables for the years 2010 to 2018. Two models were estimated, one for each set of standards, and the analysis of relevance was based on the R2 values. The results were consistent with the expectations and they suggest that IFRS information (EPS and BVPS) is more value relevant to the investor when making investment decisions, suggesting a positive effect in the adoption of IFRS for Brazil. On the other hand, equity has a higher explanatory power than profit. Thus, as the disclosure of information is not necessarily simultaneous in Bacen and IFRS, although there is an influence of Bacen’s previous information in IFRS price, the results show an incremental information contained in IFRS information. All results show the positive effect of adopting international accounting standards, which is an information aimed at the investor. It seems that the central bank has already has already recognized the positive effect. After all, from in was the CMN Resolution No. 4818 which instituted the IFRS model as the only accounting standard for consolidated statements from 2021 onwards, while Bacen standard will be restricted to individual statements.